Perancangan Website Sekolah dengan Metode SDLC V-Shape - Aklani, Syaeful Anas; Tan, Tony; Fernando, Rio (Universitas Internasional Batam, 2023)
SDS Kristen Tabqha is an elementary school in Batam city. Tabqha Christian Elementary School is located at Center Park Complex, Baloi Park, Batam City Sub-District, Batam City Prov. Riau Islands. Tabqha Christian Elementary School currently does not have a website, so information about academic and non-academic activities carried out by ordinary schools can only be obtained directly at the school. Therefore, the search for school information is not well organized and the accessibility of information is very difficult. The author aims to provide solutions to the problems that occur at Tabqha Christian Elementary School. The research methodology used to study this research includes the use of the V-Shape SDLC method and data collection through observation and interviews. This school website is built on the front-end using XAMPP, PHP programming language, Java Script, and Visual Studio Code as a code editor. With this school website, the general public can get online information about Tabqha Christian Elementary School which can be accessed anytime and anywhere.